Strategic partnership at the minilateral level: the case of South Africa's dual membership of IBSA and BRICS - Chidley, Colleen Alison Esme (My University, 2015)
The literature on International Relations purports that the proliferation of strategic partnership, particularly at the minilateral level, is explained with reference to the inherent characteristics of this latest archetype of international alignment. Although it is generally accepted that it is the inherent characteristics of strategic partnership that make it an effective diplomatic and political tool through which states can strategically position themselves in a shifting global arena, this assumption has yet to be validated. The aim of this research study is to elucidate the extent to which, and how, strategic partnership at the minilateral level impacts upon the global strategic position(ing) (GSP) of its member states. Combining universal comparison in case study methodology with constructivist perspectives, South Africa’s dual membership of the India-Brazil-South Africa (IBSA) Dialogue Forum and the Brazil-Russia-India- China-South Africa (BRICS) Forum are used to test the hypothesis that strategic partnership at the minilateral level enhances the GSP of its member states. The considerable overlap in membership of IBSA and BRICS yields two related research questions addressed in this study; what it is that India, Brazil and South Africa are better suited to achieve through IBSA without China and Russia; and what it is that China and Russia (the two BRICS members not in IBSA) bring to the table. The findings of this research study reveal that membership of IBSA and of BRICS has made a positive impact upon South Africa’s GSP according to the three strengths by which GSP is measured. However, the impact of IBSA on South Africa’s GSP is limited and largely confined to the diplomatic arena, while in the case of BRICS the impact is more significant and cuts across the diplomatic, political, economic and social spheres. As part of these findings, the particular issue-areas in which IBSA and BRICS respectively make a discernible impact upon South Africa’s GSP are identified. These findings show that IBSA and BRICS are better suited to dealing with different issue areas, which enables the two forums to be considered sui generis entities on separate but parallel tracks. Further than this, the findings provide valuable insight into South Africa’s strategic approach to international politics in the 21st Century; in particular how South Africa seeks to leverage its soft power in the international system through the intensification of its network power. More significantly, though, at the theoretical level these findings show that strategic partnership at the minilateral level is not by itself sufficient to strengthen the GSP of its member states. Instead, the extent to which a strategic partnership has an impact upon a member state’s GSP is determined by the particular composition of that minilateral alignment; that is to which particular states are (minimally) essential to achieving a particular identified mutually desired outcome. Thus, a smarter more targeted approach to minilateral alignments may well rest not only in a “magic number” but, more crucially, in their composition.
A thesis submitted to the Wits School of Social Science, Faculty of Humanities, University of the Witwatersrand in fulfillment of the requirements for the degree of Doctor of Philosophy Johannesburg 2015
Keywords: International Relations; alignment; strategic partnership; minilateralism; South Africa; foreign policy; IBSA; BRICS